(untitled) (Bangladesh Journal of Bioethics, 2020)
Asian Bioethics Conference (ABC20) was held on 22-25 Nov. 2019 at DGHS (Directorate General of Health Services) auditorium, Mohakhali and NEC (National Election Commission) Auditorium, Agargoan, Dhaka. Conference was organized by Bangladesh Bioethics Society (BBS) in cooperation of DGHS, Ministry of Health & Family Welfare; Social Science Research Council Bangladesh, Ministry of Planning; Bangladesh Medical Research Council, Mohakhali Dhaka; Asian Bioethics Association (ABA) and Eubios Ethics Institute, Thailand, New Zealand’s and Japan. Mr MA Mannan MP, Honorable Planning Minister, Government of the People’s Republic of Bangladesh was the Chief Guest. Dr. Md. Murad Hassan MP, Honorable State Minister, Ministry of Information, Government of the People’s Republic of Bangladesh was present as Special Guest. Md. Nurul Amin, Secretary, Planning Division, Ministry of Planning and Dr Iqbal Kabir, Director, Planning, Monitoring, & Research and Coordinator, DGHS were also present as Special Guests. Acknowledgement: We acknowledge our gratitude to Directorate General of Health Services (DGHS), Ministry of Healthy and Family Heath Welfare, Government of People Republic of Bangladesh to publish the news of 20 Asian Bioethics Conference in the Policy Brief. We also express our thanks to DGHS for their co-operation and collaboration during Conference.